The Crucified Boy in Russian War Propaganda: How is Theology NOT Ideology? - Tolstoj, Katya (Handelingen: Tijdschrift voor Praktische Theologie en Religiewetenschap, 2023)
The very first thing I heard when starting my studies in 1993 at the protestant Theological University in Kampen, the Netherlands, was about Theology after Auschwitz (Theologie nach Auschwitz): how it helped confront the legacy of violence and change mindsets in post-Nazi Germany. Coming from the Soviet Union, I immediately began to hope that a similar theological reflection on the Soviet past might start soon. As no such reflection emerged during the following twenty years, I gradually came to understand that I myself had to start a project to contribute to a systematical re-orientation in the post-Soviet countries. Thus, such had become my task and my calling. In 2016 I launched a project called ‘Theology after Gulag’, which name I have changed to ‘Theology after Gulag, Bucha, and beyond’ since Russia’s war in Ukraine.